Factors Controlling the Dissolved 137Cs Seasonal Fluctuations in the Abukuma River Under the Influence of the Fukushima Nuclear Power Plant Accident. Issue 1 (24th January 2022) - Igarashi, Yasunori; Nanba, Kenji; Wada, Toshihiro; Wakiyama, Yoshifumi; Onda, Yuichi; Moritaka, Shota; Konoplev, Alexei
Abstract: The 2011 Fukushima Daiichi Nuclear Power Plant (FDNPP) accident released large amounts of radioactive materials into the environment. River systems play an important role in the terrestrial redistribution of FDNPP‐derived 137 Cs in association with water and sediment movement. We examined the seasonal fluctuations in dissolved and particulate 137 Cs activity concentrations and clarified the biological and physicochemical factors controlling 137 Cs seasonality in the Abukuma River's middle course in the region affected by the FDNPP accident. The results showed seasonal fluctuations in the dissolved 137 Cs activity concentration, with an increase in summer and a decrease in winter, although there was no clear seasonal change in the particulate 137 Cs activity concentration. Water temperature and K + concentration dominated the seasonality of the dissolved 137 Cs activity concentration. The volumetric activity concentration of the organically bound 137 Cs was found to be several orders of magnitude lower than that of the dissolved 137 Cs. Therefore, we concluded that the 137 Cs in organic matter is not a source of dissolved 137 Cs in river water. The study also revealed the temperature dependence of K d in riverine environments from a Van't Hoff equation. The standard reaction enthalpy of 137 Cs in the Abukuma River was calculated to be approximately −19.3 kJ/mol. This was the first study to clearly reveal the mechanisms by which the dissolved 137 Cs activity concentration and K d are influenced by chemical and thermodynamic processes in the middle course of a large river, and it is expected to lead to an improved model of 137 Cs dynamics in rivers. Plain Language Summary: The 2011 Fukushima Daiichi Nuclear Power Plant (FDNPP) accident released large amounts of radioactive materials into the environment. River systems play an important role in the terrestrial redistribution of FDNPP‐derived 137 Cs in association with water and sediment movement. The dissolved 137 Cs activity concentration in the Abukuma River showed clear seasonal fluctuations, with an increase in summer and a decrease in winter, although there was no clear seasonal change in the particulate 137 Cs activity concentration. Water temperature and K + concentration dominated the seasonality of the dissolved 137 Cs activity concentration. Previously, decomposition of 137 Cs‐contaminated organic matter was thought to be the reason for the seasonality of the dissolved 137 Cs activity concentration in rivers. However, in the middle course of the river, the organically bound 137 Cs activity concentration is much lower than that of the dissolved 137 Cs activity concentration, indicating that the decomposition of organic matter does not directly affect the dissolved 137 Cs in the middle course. This study revealed that seasonal fluctuations in river temperature determine the seasonality of the dissolved 137 Cs activity concentration in the middle course in the region affected by the FDNPP accident. Key Points: Dissolved 137 Cs in the Abukuma River displays significant seasonal fluctuations The main factors determining the seasonality of dissolved 137 Cs activity concentrations are water temperature and K + The standard enthalpy of 137 Cs desorption from sediments was determined to be approximately −19.3 kJ/mol